2012
DOI: 10.1587/elex.9.795
|View full text |Cite
|
Sign up to set email alerts
|

ReRAM technology; challenges and prospects

Abstract: Abstract:We review recent progresses in Resistive Random Access Memory (ReRAM) technologies together with difficult challenges and prospects. ReRAM is one of the most promising emerging nonvolatile memories, in which both electronic and electrochemical effects play important roles in the nonvolatile functionalities. First, a brief historical overview of the research is provided. The technological overview is reported with the epoch-making achievements. Second, the current understanding in terms of the operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Nowadays, the NVM market is dominated by the silicon-based Flash. However, there are a few drawbacks for Flash, including scaling M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT issue, relatively slow operation speed, and high voltage for program/erase operations [2]. Even though the three-dimensional crossbar structure may solve the low-density issue of Flash temporarily [3], the market demands next-generation NVM that has overall advantages over Flash.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the NVM market is dominated by the silicon-based Flash. However, there are a few drawbacks for Flash, including scaling M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT issue, relatively slow operation speed, and high voltage for program/erase operations [2]. Even though the three-dimensional crossbar structure may solve the low-density issue of Flash temporarily [3], the market demands next-generation NVM that has overall advantages over Flash.…”
Section: Introductionmentioning
confidence: 99%
“…The academic and industrial research topics on RRAM cover quite a wide range: materials problem, RS mechanism, manufacture, integration, and even other function beyond the data storage, as reviewed previously [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In this review article, we concentrate on the materials science issue including the material selection and the corresponding RS mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the redox reaction at Pt/NiO interface contributes to the ReRAM switching 45 as reported in other materials. 38,39 After realization of in-situ forming-reset-set processes, composition analysis within filaments, especially at the vicinity of the Pt/NiO interface, will make clear information on the switching mechanism. Although the forming process was clearly recognized, the reset operation was not found in the TEM instrument where the ambient is a vacuum.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, binary oxides showing the unipolar as well as bipolar switching generally need the forming process while the ReRAM device with very thin oxide layer occasionally does not need this process. 38,39 The devices are easily eternally broken during the forming process where a high level of electricity is used, and the in-situ TEM observation is thought to be hard as pointed out by Schroeder et al 40 In a work on Ti-O by Kwon et al, 41 they observed a phase transformation in a filament during the set and reset operation. It was pointed out this phase transformation between the conductive Magneli phase and other insulating phase contributes to the ReRAM switching.…”
Section: Introductionmentioning
confidence: 99%
“…Non-volatile memories have become a key technology to realize the advanced electronic devices especially for the portable electronics applications [1,2,3]. Further scaling and integration of non-volatile memories would be required such as 4 tera bits for multi-level cell (MLC) and 8 tera bits for triple-level cell (TLC) with 22 nm technology node in 2028 [4].…”
Section: Introductionmentioning
confidence: 99%